Application of Health Law in Narcotics Rehabilitation Programs by Reporting Recipient Institutions - Indra Kurniyawan; Marice Simarmata; T Riza Zarzani N (Yayasan Multidimensi Kreatif, 2025)
Abusers and victims of narcotics abuse have the right to receive rehabilitation in accordance with applicable regulations. The application of health law in narcotics rehabilitation programs by Mandatory Reporting Institutions (IPWL) is a very important effort in helping abusers and victims of narcotics abuse. The program focuses not only on physical recovery from medical problems, but also on mental and social recovery. IPWLs appointed by the government must carry out rehabilitation programs for abusers and victims of narcotics abuse in accordance with the standards that have been set. The goal is to restore the condition of abusers and victims of narcotics abuse so that they can integrate themselves back into society and function socially. The standard of rehabilitation services set by the government covers various aspects such as methods, duration, facilities, and costs, this aims to ensure that each individual receives treatment that suits his or her needs. The legal framework underlying this program is Law No. 35 of 2009 concerning Narcotics and Permenkes No. 17 of 2023 concerning Amendments to Permenkes No. 4 of 2020 concerning the Implementation of IPWL. Minister of Health Regulation No. 17 of 2023 which requires medical and social rehabilitation for abusers and victims of narcotics abuse. Through a normative juridical approach, this study highlights various problems regarding the application of health law for abusers and victims of narcotics abuse, therapy for appropriate treatment, and understanding the financing mechanism of accepted therapies. The results of this study are expected to be able to provide an analysis of the effectiveness of the implementation of health law, as well as identify appropriate therapies in the rehabilitation of drug abusers and victims of drug abuse and understand the mechanism in financing it.